Combined Intraperitoneal and Intrathecal Etanercept Reduce Increased Brain Tumor Necrosis Factor-Alpha and Asymmetric Dimethylarginine Levels and Rescues Spatial Deficits in Young Rats after Bile Duct Ligation - Sheen, Jiunn-Ming; Chen, Yu-Chieh; Hsu, Mei-Hsin; Tain, You-Lin; Yu, Hong-Ren; Huang, Li-Tung (Frontiers in Cellular Neuroscience, 2016)
Background: Rats subjected to bile duct ligation (BDL) exhibit increased systemic oxidative stress and brain dysfunction characteristic of hepatic encephalopathy, including fatigue, neurotransmitter alterations, cognitive and motor impairment, and brain inflammation. The levels of tumor necrosis factor-alpha (TNF-α) and asymmetric dimethylarginine (ADMA) are both increased in plasma and brain in encephalopathy induced by chronic liver failure. This study first determined the temporal profiles of TNF-α and ADMA in the plasma, brain cortex, and hippocampus in young BDL rats. Next, we examined whether etanercept was beneficial in preventing brain damage. Methods: Young rats underwent sham ligation or BDL at day 17 ± 1 for 4 weeks. Treatment group rats were administered etanercept (10 mg/kg) intraperitoneally (IP) three times per week with or without etanercept (100 µg) intrathecally (IT) three times in total. Results: We found increased plasma TNF-α, soluble tumor necrosis factor receptor 1, soluble tumor necrosis factor receptor 2, and ADMA levels, increased cortical TNF-α mRNA and protein and ADMA, and hippocampal TNF-α mRNA and protein, and spatial defects in young BDL rats. The increase in cortex TNF-α mRNA and ADMA were reduced by IP etanercept or combined IP and IT etanercept. Dually IP/IT etanercept administration reduced the increased cortical and hippocampal TNF-α mRNA and protein level as well as spatial deficits. Conclusions: We conclude that combined intraperitoneal and intrathecal etanercept reduce increased brain TNF-α and ADMA levels and rescues spatial deficits in young rats after BDL.